REFLEKSI PENDIDIKAN IPA SEKOLAH DASAR DI INDONESIA (Relevansi Model Pendidikan Paulo Freire dengan Pendidikan IPA di Sekolah dasar) - Anatri Desstya; Istiani Indah Novitasari; Aldi Farhan Razak; Kukuh Sandy Sudrajat (Profesi Pendidikan Dasar, 2017)
This study aimed to describe: the process of science education in elementary schools in line with expectations at this time, the educational model Paulo Freire, the purpose of education Paulo Freire, and its relevance to science education in primary schools. This study is a library research. The main data sources obtained from books, journals and other writings related to science education in primary schools and the educational model of Paulo Freire. Data collection techniques with identifying information of the books, previous research reports, journals, articles, web, or other information. This research uses descriptive analysis method.The data analysis includes the decomposition of matter suitable object of study then described and analyzed for the conclusion, namely 1) science education in elementary routed through direct experience, conducted inquiry scientifically develop process skills and scientific attitude,2) educational model’s Paulo Freire states on education dialectical, liberating education and shackled, and educational humanism, 3) he conformity of Paulo Freire's education with science education in elementary school, namely in the change in the quality of critical thinking, 4) Relevance between the two in concepts, goals, positions of educators and learners.